1989
DOI: 10.1095/biolreprod41.5.933
|View full text |Cite
|
Sign up to set email alerts
|

An Abnormal Pattern of Embryonic Development during Early Pregnancy in Aging Rats1

Abstract: There is recent evidence that a decline in fertility and litter size precedes the cessation of regular estrous cyclicity in middle-aged female rats. This decline in litter size is related to a decrease in the number of normal blastocysts that are present on Day 5 of gestation, immediately prior to implantation. Thus, the pattern of embryonic development during the first 5 days of pregnancy may be altered in middle-aged rats, resulting in fewer implanting embryos and smaller litter sizes. The present study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
1
7
1
2
Order By: Relevance
“…Reasons for the reduced fertility in this group of aging rats are, possibly, a failure in folliculogenesis due to a depletion or the drastically reduced size of the pool of ovarian follicles, as well as an age-induced decrease in sensitivity to the ovulation induction signal (LH/hCG) in the presence of normal folliculogenesis, leading to a lower number of oocytes ovulated in some cases. Our results are in contrast to those of Day et al (1989) who reported that there was no difference in the numbers of fertilized oocytes retrieved in the 4-to 5-, 10-, and 13-month-old, non-stimulated Long-Evans rats. This discrepancy could arise from differences in age and rat strains.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Reasons for the reduced fertility in this group of aging rats are, possibly, a failure in folliculogenesis due to a depletion or the drastically reduced size of the pool of ovarian follicles, as well as an age-induced decrease in sensitivity to the ovulation induction signal (LH/hCG) in the presence of normal folliculogenesis, leading to a lower number of oocytes ovulated in some cases. Our results are in contrast to those of Day et al (1989) who reported that there was no difference in the numbers of fertilized oocytes retrieved in the 4-to 5-, 10-, and 13-month-old, non-stimulated Long-Evans rats. This discrepancy could arise from differences in age and rat strains.…”
Section: Discussioncontrasting
confidence: 99%
“…The decline in pregnancy rates and litter size in aging rodents could be attributed to DNA fragmentation in oocytes in aging mice (Fujino et al, 1996), as well as the altered embryonic developmental pattern in aging rats (Day et al, 1989). Volarcik et al (1998) reported that the quality of the oocytes retrieved from women of 35 years and above was compromised.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, embryos from old animals showed a developmental delay before and during implantation [10,11,13]. Similar results were obtained in the aged rats [21]. Increment of retarded embryos in the aged animals may be an indication of the less viable embryos, probably resulting from the delay of ovulation [17] and abnormal fertilization [11,12,17].…”
Section: Discussionsupporting
confidence: 72%
“…Young adult Per mutant females show the same oestrous cycle pattern lasting 4-5 days as wild-type females (unpublished data). This regularity in oestrus cyclicity provides a hint for the regularity in the rhythmicity of the luteinizing hormone (LH) surge and ovarian hormones facilitating fertility and embryonal development (Day et al 1989, Diaz et al 2000, Wise et al 2002, Miller et al 2004, Nelson 2005. Contrary to this, adult Clock mutant females reveal prolonged irregular cycles associated with elevated rates of foetal reabsorption and pregnancy failures (Miller et al 2004, Kennaway 2005, Dolatshad et al 2006.…”
Section: Discussionmentioning
confidence: 99%